Oswald Mosley and the British Union of Fascists: A Brief Historiographical Inquiry - McCloud, Nedra (History compass, 2006)
The historiography of the rise and fall of Oswald Mosley’s British Union of Fascists has been lively since the 1930s. The months of parliamentary debate that followed the fascist and communist violence at Mosley’s BUF rally of June 1934 at Olympia Hall in Hammersmith, London generated much soul-searching about the role of the state in keeping order in the public political arena in Britain. The significance of that "Olympia debate" in parliament and the press has itself been contested in the 1990s and in the first decade of the twenty-first century. Of late, social historians such as Julie Gottlieb have begun examining the phenomenon of British fascism by asking whether the female of the species is, after all, the more gentle and merciful of the two genders in regard to violent and racist social eruptions. With the recent release of private and governmental papers concerning Mosley and his movement, scholars are finding British fascism well worth further inquiry.